China's Foreign Trade Behavior in the 1980's : An Empirical Analysis - Brender, Adi (IMF Working Papers; Working Paper ;, 1992)
This paper studies the behavior of China's foreign trade in the 1980s. Chinese customs data are used to construct, for the first time, quarterly unit value and volume series that are then used to estimate foreign trade income and price elasticities. The estimated export supply price elasticities are negative and became even more negative after the reforms in 1985. The import price elasticity is very close to minus one. These results suggest that administrative controls still have a dominant effect on China's trade and may also suggest that reforms in the management system of Chinese enterprises were not sufficient to create profit maximizing behavior by managers.